(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2016)
Polychemotherapy and intermittent monochemotherapy regimens in metastatic breast cancer were examined in a meta analysis that included both tumor response rate and toxicities. Randomized controlled studies (conducted during 1990-2008) comparing monochemotherapy and poly-chemotherapy in advanced breast cancer patients were selected from electronic databases. Meta-analysis for response rate and toxicities [nausea and vomiting, toxic death, alopecia and reduced white cell count (WCC)] was performed using the Mantel-Haenszel method. The heterogeneity among the trials was assessed through a χ2 statistic, I2 and visual inspection of the forest plots. Analysis of eligible studies reveals statistical significant difference in response rate (OR 0.72, 95% CI 0.65-0.79), nausea and vomiting (OR 0.80, 95% CI 0.67-0.59), Alopecia (OR 0.75, 95% CI 0.64-0.88) and reduced WCC (OR 0.55, 95% CI 0.48-0.62) which favours polychemotherapy except toxic death (OR 0.87, 95% CI 0.58-1.29). There was marked evidence of heterogeneity in all end points except toxic death. This meta analysis shows the superiority of efficacy but not of safety of polychemotherapy over that of a single agent. However, the choice of treatment should be based on the response to the therapy, toxicity, patient preference, presence of metastases or imminent complications requiring aggressive and rapid tumor control.